2017
DOI: 10.5603/cj.a2017.0021
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of central thrombus in hemodynamically stable patients with pulmonary embolism

Abstract: The present study showed that central thrombus was not an independent predictor of mortality in hemodynamically stable PE patients. LMWH and UFH were similarly effective in the treatment of this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
(24 reference statements)
0
5
1
4
Order By: Relevance
“…The relationship between syncope and PTE mortality is not clear in the literature. Senturk et al reported the syncope frequency was 2‐times higher in patients with syncope despite it was not associated with the mortality . In our study, although there was a 2‐fold increase in syncope, there was no statistical difference.…”
Section: Discussioncontrasting
confidence: 65%
“…The relationship between syncope and PTE mortality is not clear in the literature. Senturk et al reported the syncope frequency was 2‐times higher in patients with syncope despite it was not associated with the mortality . In our study, although there was a 2‐fold increase in syncope, there was no statistical difference.…”
Section: Discussioncontrasting
confidence: 65%
“…The primary proposed mechanism is based on the presence of a large pulmonary artery embolus with greater than 50% occlusion of the pulmonary vascular tree accompanied by RVD and consecutively impaired left ventricular filling, leading to decreased cardiac output with arterial hypotension and declined cerebral blood flow resulting in syncope [19]. In our sample, the syncopal episode was not associated with a more central location of the thrombus load on chest CT examination, unlike other similar studies [22,23]. We, therefore, hypothesize that an equally important pathophysiological mechanism could be the partial resolution or displacement of the thrombus load, which might explain the incidence of syncope in our study population.…”
Section: Discussionmentioning
confidence: 59%
“…Thrombus localization on computed tomography of the chest was classified as peripheral (isolated lobar, segmental, and/or subsegmental arteries) or central [22].…”
Section: Definitionsmentioning
confidence: 99%
“…Остальные факторы, такие как ВБНК и ЗНО, выявлялись реже, в 11,4% и 6,3% случаев соответственно. Влияние на прогноз различной локализации тромбоза легочных сосудов еще требует изучения [6][7][8]. В нашем исследовании двустороннее поражение легких при ТЭЛА встречалось чаще (р<0,05) в сравнении с односторонней женщины 1 группы в сравнении с женщинами 3 группы, лицами старше 45 лет (р=0,005).…”
Section: обсуждение и результатыunclassified